EFEKTIFITAS KONSEP RUANG EKSTRA SEBAGAI ALTERNATIF MITIGASI PENJALARAN TSUNAMI DI SUNGAI - Rajuli Amra (Jurnal Teknik Sipil, 2020)
Tsunami could penetrate up far upstream of the river and brought serious damage to in-river structures and flooded the residential area. Mitigating propagated wave conventionally by raising the river embankment was ineffective and amplified tsunami force in the river. Relocating the river embankment in specific configuration which resulted the “extra room”, succesfuly dissipate the tsunami flow in river. The effectivity of this approach was constrained by room capacity and layout. This research investigated the most effective layout for “extra-room” application against tsunami in the meandering river. The investigation conducted numerically using COMCOT model to simulate 60-minutestsunami for 2m wave height. The symmetric moderate sinous-river planform (θ0=600, length=1 km, withd= 0,4 km) was modelled using sine-generated curve, while the bed topography adopted the tranversal bed elevation concept. Using the stiff-assumption for various layout scenario, the result revealed that along-river enlargement proved more effective in dissipating the tsunami height by 63%, compare to lateral-river expansion. In addition, enlarging the river capacity at the inflection point gave less effect, compare than widening the room at the river mouth area. The applicability of the proposed mitigation concept was not applied universally, in which the embankment overtopping and riverine inundation might still occur when intial tsunami wave height exceeds the tsunami design amplitude.